Tree Diseases in Kansas - Tisserat, Ned A. (My University, 1999)
This publication describes how to diagnosis shade trees in Kansas and how to control the pathogens that affect the trees.
C674_1999_04
Keywords: C674; Forestry; Environment and Natural Resources; C